Kappa opioid signaling in the central nucleus of the amygdala promotes disinhibition and aversiveness of chronic neuropathic pain. Issue 4 (April 2019) - Navratilova, Edita; Ji, Guangchen; Phelps, Caroline; Qu, Chaoling; Hein, Matthew; Yakhnitsa, Vadim; Neugebauer, Volker; Porreca, Frank
Abstract : Abstract: Chronic pain is associated with neuroplastic changes in the amygdala that may promote hyper-responsiveness to mechanical and thermal stimuli (allodynia and hyperalgesia) and/or enhance emotional and affective consequences of pain. Stress promotes dynorphin-mediated signaling at the kappa opioid receptor (KOR) in the amygdala and mechanical hypersensitivity in rodent models of functional pain. Here, we tested the hypothesis that KOR circuits in the central nucleus of the amygdala (CeA) undergo neuroplasticity in chronic neuropathic pain resulting in increased sensory and affective pain responses. After spinal nerve ligation (SNL) injury in rats, pretreatment with a long-acting KOR antagonist, nor-binaltorphimine (nor-BNI), subcutaneously or through microinjection into the right CeA, prevented conditioned place preference (CPP) to intravenous gabapentin, suggesting that nor-BNI eliminated the aversiveness of ongoing pain. By contrast, systemic or intra-CeA administration of nor-BNI had no effect on tactile allodynia in SNL animals. Using whole-cell patch-clamp electrophysiology, we found that nor-BNI decreased synaptically evoked spiking of CeA neurons in brain slices from SNL but not sham rats. This effect was mediated through increased inhibitory postsynaptic currents, suggesting tonic disinhibition of CeA output neurons due to increased KOR activity as a possible mechanism promoting ongoing aversive aspects of neuropathic pain. Interestingly, this mechanism is not involved in SNL-induced mechanical allodynia. Kappa opioid receptor antagonists may therefore represent novel therapies for neuropathic pain by targeting aversive aspects of ongoing pain while preserving protective functions of acute pain. Abstract : Blockade of kappa opioid receptor signaling in the right amygdala of spinal nerve ligation rats restores presynaptic inhibitory control of CeA output neurons and relieves the aversiveness of ongoing neuropathic pain. Kappa opioid receptor antagonists may be effective for treatment of chronic neuropathic pain.